Instrumentality power: or Angola, a regional power in crisis growth - Almeida, E. C. (International Journal Advances in Social Science and Humanities, 2014)
The small following text was targeted Angola as a regional power that has not yet been hardpower can no onger be regarded as softpower in the African context in general and regional center-southern Africa in particular. For this reason we tried to develop a new theory that suits Angolan characteristics and its projection in the African context and how important vertex in political-military relations in sub-Saharan Africa.